Erosion-driven shrinkage of recently glacier-detached lakes signals a proglacial-to-paraglacial transition across the Third Pole - Qian Tang; Guoqing Zhang; Tandong Yao; Matthias Huss; Jonathan L. Carrivick; Adam Emmer; Christian Huggel; Simon Allen; Dongfeng Li; Menger Peng; Xue Wang; Shaochun Zhao; et al. (Global and Planetary Change, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Determinants of physiological demands, physiological resilience, and muscle fatigability during load carriage in women: an observational trial - Erin E. Robertson; Charlotte V. Coombs; Ella B. Halsall; Christina D. Young; Alice S. Irving; Jonathan C. Y. Tang; Julie P. Greeves; Thomas J. O’Leary (European Journal of Applied Physiology, 2026)

Scaling Laws Reveal a Unified Species‐Energy Relationship for Mountain Biodiversity - Zihan Jiang; Hongyan Liu; Zhiyao Tang; Jonathan M. Chase; Alexandre Antonelli; Michael Kessler; Maharaj K. Pandit; Kumar Manish; Wei Xu; Jianxiao Zhu; Qinggang Wang; Hang Sun; et al. (Global Ecology and Biogeography, 2026)
Aim Energy availability is often assumed to be a primary driver of variation in biodiversity across large‐scale environmental gradients such as elevation, but support for the role of energetic constraints is far from universal. Here, we assume that these variations in energy–richness relationships might arise from the degree of match between the scale of the response of organisms to energy (response scale) and the scale of the observation made (observation scale). Location 41 mountain ecosystems worldwide, with detailed case studies on Dongling Mountain, China. Time Period Contemporary. Major Taxa Studied Trees, shrubs, herbs, ferns, birds, ants, bees, Lepidoptera, Coleoptera, Orthoptera, soil fauna, litter‐layer fauna, bacteria, fungi. Methods First, we quantify the response scale on the basis of energy requirements, and then, we develop a general scaling model that explicitly describes how the scale matching between response and observation scale influences the predictive power of energy in determining elevational richness patterns; this model holds across taxonomic groups, trophic guilds, and ecosystems across mountains globally. Results Global analyses strongly supported the model's prediction that scale matching determines the detectability of energy‐richness relationships. On Dongling Mountain, energy availability best explained richness patterns at the predicted response scales for trees, herbs, and litter fauna. Main Conclusions Our model advances the understanding of montane biodiversity distributions by demonstrating the critical role of scale matching in energy–richness relationships. Our findings strongly support the existing mechanistic foundation for predicting biodiversity changes across spatial scales in montane ecosystems. The scale‐matching principle we identified is likely to be applicable to a wide range of taxa and other ecosystems where energy availability varies across scales.

Multi‐Model Ensembles in Ecosystem Modeling: Challenges and Best Practices for Decision‐Making - Kaiyu Guan; Rongzhu Qin; Zewei Ma; Lei Zhao; Licheng Liu; Sheng Wang; Trevor F. Keenan; Mengqi Jia; Debjani Sihi; Eric Potash; Senthold Asseng; Jingyun Tang; et al. (Global Change Biology, 2026)
Ecosystem models are increasingly central to the decision‐making for environmental policy, conservation planning, and climate‐related investments. Yet, the growing reliance on Multi‐Model Ensembles (MMEs) of ecosystem models by practitioners and policymakers, sometimes under tight timelines and imperfect information, has frequently outpaced the scientific rigor required to ensure ensemble reliability. Here, MMEs refer to approaches that combine targeted predictions from multiple models with the expectation of improving robustness and quantifying predictive uncertainty. Poorly designed MMEs may create a false sense of confidence and lead to suboptimal policy and market decisions. This perspective argues that robust decision‐making‐relevant MMEs must be grounded on two pillars: (1) rigorous Model Intercomparison Projects (MIPs), which identify inter‐model agreement and disagreement, characterize model uncertainties, and evaluate robustness with observationally based benchmarks—MIPs' diagnostic evaluation is so critical that it must be needed to drive MME's decision in model selection and weighting, especially when only a limited number of models available; and (2) co‐design by both stakeholders and scientists to ensure that scenarios, metrics and uncertainty requirements provide decision‐relevant information. Building upon the past success and lessons from the existing MIPs‐MMEs efforts (e.g., climate/Earth system/crop), we derived the theoretical basis for MMEs, addressed their specific challenges in ecosystem modeling, and highlighted proper consideration of model numbers and diversity, risk of model inter‐dependence, effective calibration of model parameters, possible overdue of some ecosystem model development, critical roles of open benchmark data across a wide range of conditions, and suggested use of Artificial Intelligence to support MIPs‐MMEs. We highlighted the under‐recognized opportunity for MIPs and MMEs to drive scientific progress and innovation through identifying better performing models, systematic benchmarking, feedback loops, and targeted model improvement. By following actionable best practice guidelines, MMEs can evolve from ad hoc aggregation of models into a trusted backbone of environmental policy and decision‐making.

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pulmonary effect of 2D MXenes in mice: Immune cell responses and disrupted hematopoiesis - Gang Tang; Min Li; Jiexia Cheng; Ziniu Wang; Guangxuan Wang; Jianbo Shi; Jonathan W.C. Wong; Jie Gao; Dou Wang; Guohao Zhang; Li Zeng; Yanhua Wang; et al. (NanoImpact, 2026)

Evaluation of the slope of inverse creatinine to define progressive chronic kidney disease in cats and associated risk factors - Pak-Kan Tang; Rosanne E. Jepson; Yu-Mei Chang; Jonathan Elliott (The Veterinary Journal, 2026)

Dissolved organic matter enhances sunlight-induced transformation of tire rubber antioxidant 6PPD to 6PPD-quinone in aquatic environments - Minghan Zhu; Wenyan Yu; Zhujun Luo; Jonathan W.C. Wong; Shaoyu Tang; Zhen Yu; Zhi Dang; Junfeng Niu (Water Research, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Dynamics and bifurcation of a hybrid competition model with applications to adaptive cancer therapy - Huansheng Sun; Biao Tang; Jonathan E. Forde; Yanni Xiao (Mathematical Biosciences, 2026)

A stimuli-responsive polymeric ferroptosis drug delivery system for treatment of liver metastases - Deqiang Deng; Muyang Yang; Zhen Zeng; Tianbing Xu; Yuanyuan Geng; Weicheng Tang; Yao Sun; Jonathan F. Lovell; Lisen Lu; Mingxin Zhu; Honglin Jin (Chemical Engineering Journal, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Including Dispersive Shear Stress in Urban Environments for Single Column Dispersion Models - Jonathan Retter; David Heist; Michael Pirhalla; R. Chris Owen; Wei Tang; Terrance Odom; Lydia Brouwer (Boundary-Layer Meteorology, 2025)

Exposure of Australian dams to seismic hazard from proximal faults - Mark Quigley; Tim Werner; Yuxiang Tang; Dan Clark; Jonathan Griffin; Haibin Yang (Environment Systems and Decisions, 2025)
The purpose of this study is to obtain estimates of ground surface rupture and ground motion hazards at standardised scales useful for general reference and regional comparisons of dams (n = 548) registered with the Australian National Committee on Large Dams (ANCOLD). Geospatial and statistical methods are used to investigate the exposure of dams to seismic hazard from 409 faults in the Geoscience Australia Neotectonic Features Database (NFD). We identify 216 faults at distances less than 100 km from 428 dams and measure 4055 fault-to-dam distances. At least 31 dams are located within 1 km of NFD fault traces and at least 16 of these dams could reside within NFD primary fault zones. Estimates of NFD maximum moment magnitudes (M w,max ) from fault area and length regressions range from 5.6 ≤ M w ≤ 7.9. Average (AD) and maximum (MD) NFD fault displacements for M w,max events range from 0.3 m ≤ AD ≤ 4.4 m and 0.9 m ≤ MD ≤ 8.4 m. Distance-probability regressions for distributed ground surface rupture suggest approximately 40 dams have a ≥ 10% probability of ground surface rupture occurring in the area encompassing the dam in a M w,max event. Peak ground accelerations (PGA) and pseudo-spectral acceleration at 1.0 s (PSA[1.0 s]) are estimated for M w,max at dam sites using the same set of ground motion models (GMMs) for the 2023 National Seismic Hazard Assessment (NSHA23), assuming engineering rock site conditions with a time-averaged shear wave velocity between the surface and 30 m sediment depth (VS30) of 760 m/s. Of the 4055 M w,max scenarios considered in total, 3579 M w,max scenarios produce 85th percentile PGA ≥ 0.1 g at dam sites and 2844 scenarios produce 85th percentile PSA[1.0 s] ≥ 0.1 g. Comparison with 1:5,000 annual exceedance probability (AEP) PGA and PSA[1.0 s] estimates from the NSHA23 indicate there are 404 out of 428 dams where NFD M w,max PGA are greater than NSHA23 values, and 422 instances where PSA[1.0] > NSHA23. Proximity to NFD faults imparts a first-order control on relative hazard. A large increase in the number of identified NFD faults over the last decade suggests further research will continue to increase NFD fault populations. NFD fault slip rates and M w,max are important parameters in seismic hazard analysis for many dams but exhibit large epistemic and aleatoric uncertainties. Improving the characterisation of NFD faults through acquisition of direct fault-specific seismic hazard information (e.g., single-event displacements, slip rates, inter-event times, frequency-M w distributions, segmentation scenarios) will assist with hazard profiling for many ANCOLD dams.

Enhanced simulated sunlight photolysis of antibiotics on soil surfaces by biochar: Effects and mechanisms - Yuying Wu; Dengmiao Cheng; Jisen Xiong; Shaoyu Tang; Jonathan Woon Chung Wong; Zhaojun Li (Journal of Environmental Management, 2025)

Fibroblast growth factor 23 – A review with particular reference to the physiology and pathophysiology of phosphate homeostasis in the cat - Jonathan Elliott; Pak Kan Tang (The Veterinary Journal, 2025)

Cardiac pathology associated with hypertension and chronic kidney disease in aged cats - Zara Flora; Pak K. Tang; Ken Smith; Jonathan Elliott (Journal of Comparative Pathology, 2025)

Training with reduced carbohydrate availability affects markers of bone resorption and formation in male academy soccer players from the English Premier League - Reuben Stables; Liam Anderson; Craig Sale; Marcus P. Hannon; Rachel Dunn; Jonathan C. Y. Tang; William D. Fraser; Nessan B. Costello; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2024)
Purpose To test the hypothesis that training with reduced carbohydrate (CHO) availability increases bone resorption in adolescent soccer players. Methods In a randomised crossover design, ten male players (age: 17.4 ± 0.8 years) from an English Premier League academy completed an acute 90-min field-based training session (occurring between 10:30–12:00) in conditions of high (TRAIN HIGH; 1.5 g.kg −1 , 60 g, 1.5 g.kg −1 and 1.5 g.kg −1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW; 0 g.kg −1 ). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TRAIN LOW. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone resorption (βCTX), bone formation (PINP) and calcium metabolism (PTH and ACa). Results External training load did not differ (all P > 0.05) between TRAIN HIGH and TRAIN LOW, as evident for total distance (5.6 ± 0.8; 5.5 ± 0.1 km), average speed (81 ± 9; 85 ± 12 m.min −1 ) and high-speed running (350 ± 239; 270 ± 89 m). Area under the curve for both βCTX and PINP was significantly greater ( P < 0.01 and P = 0.03) in TRAIN LOW versus TRAIN HIGH, whilst no differences in PTH or ACa ( P = 0.11 and P = 0.89) were observed between all three trials. Conclusion CHO restriction before, during and after an acute soccer training session increased bone (re)modelling markers in academy players. Despite acute anabolic effects of bone formation, the long-term consequence of bone resorption may impair skeletal development and increase injury risk during growth and maturation.

Degradation and detoxification of 6PPD-quinone in water by ultraviolet-activated peroxymonosulfate: Mechanisms, byproducts, and impact on sediment microbial community - Wenyan Yu; Shaoyu Tang; Jonathan W.C. Wong; Zhujun Luo; Zongrui Li; Phong K. Thai; Minghan Zhu; Hua Yin; Junfeng Niu (Water Research, 2024)

Degradation of tris(1,3-dichloro-2-propyl) phosphate (TDCPP) by ultraviolet activated hydrogen peroxide: Mechanisms, pathways and toxicity assessments - Zhujun Luo; Lizhu Yuan; Jonathan W.C. Wong; Minghan Zhu; Yuanyuan Yu; Kai Wang; Hua Yin; Shaoyu Tang; Junfeng Niu (Chemical Engineering Journal, 2024)

Co–elevation of CO2 and temperature enhances nitrogen mineralization in the rhizosphere of rice - Jinyuan Zhang; Zhenhua Yu; Yansheng Li; Guanghua Wang; Xiaobing Liu; Caixian Tang; Jonathan Adams; Junjie Liu; Judong Liu; Shaoqing Zhang; Junjiang Wu; Jian Jin (Biology and Fertility of Soils, 2024)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

A scalable framework for quantifying field-level agricultural carbon outcomes - Kaiyu Guan; Zhenong Jin; Bin Peng; Jinyun Tang; Evan H. DeLucia; Paul C. West; Chongya Jiang; Sheng Wang; Taegon Kim; Wang Zhou; Tim Griffis; Licheng Liu; et al. (Earth-Science Reviews, 2023)

Elevational shift in seed plant distributions in China's mountains over the last 70 years - Kuiling Zu; Jonathan Lenoir; Jingyun Fang; Zhiyao Tang; Zehao Shen; Chengjun Ji; Chengyang Zheng; Ao Luo; Wenqi Song; Niklaus E. Zimmermann; Loïc Pellissier; Zhiheng Wang (Global Ecology and Biogeography, 2023)
Aim Significant changes in species elevational ranges in mountains have been repeatedly documented, yet the direction, magnitude and drivers of these shifts remain controversial. Presently, there is still lacking evidence about the general nature of species elevational range shifts in eastern Eurasia in response to anthropogenic climate change. By using historical specimen records and recent field observations for 735 seed plant species across 29 China's mountains, we assessed changes in species' elevational centroids and their drivers. Location China. Time Period 1950–2018. Major Taxa Studied Seed plant species. Methods The elevation records of all sampled occurrences in each mountain during the two time periods were estimated, and the null models were developed to test the sampling bias. Ecological niche models (ENMs) were used to evaluate the relative importance of climate factors in constraining each species distribution. Generalized linear models (GLMs) to test the relationships between the centroid elevational range shifts of species and different divers. Results We found that 54% of the species shifting upward and 46% downhill. However, species' elevational shifts significantly differed among species and mountains. Herbaceous and lowland species moved upward faster than woody and high‐elevation species. Species in temperate mountains and in mountains with taller elevational gradients moved upward, while species in subtropical mountains and in mountains with shorter elevational gradients moved downward. Precipitation changes experienced by species, species' climatic adaptations, several species' functional traits and mountain size all contributed to explain the magnitude of species' centroid elevational range shifts. Main Conclusions Our results highlight complex biodiversity redistribution of seed plants across Chinese mountains, not necessarily conforming to the trend of species upward shifts in elevation. Changes in precipitation regimes may blur the simplistic assumption of isotherm tracking. This study fills an important geographic shortfall for our understanding of biodiversity redistribution under anthropogenic climate change.

Grazing reduces plant sexual reproduction but increases asexual reproduction: A global meta-analysis - Mi Wentao; Tang Shiming; Qi Le; Ren Weibo; Ellen L. Fry; Jonathan R. De Long; Reuben C.P. Margerison; Chi Yuan; Liu Xiaomin (Science of The Total Environment, 2023)

Assessing long‐term impacts of cover crops on soil organic carbon in the central US Midwestern agroecosystems - Ziqi Qin; Kaiyu Guan; Wang Zhou; Bin Peng; Jinyun Tang; Zhenong Jin; Robert Grant; Tongxi Hu; María B. Villamil; Evan DeLucia; Andrew J. Margenot; Mishra Umakant; et al. (Global Change Biology, 2023)
Cover crops have been reported as one of the most effective practices to increase soil organic carbon (SOC) for agroecosystems. Impacts of cover crops on SOC change vary depending on soil properties, climate, and management practices, but it remains unclear how these control factors affect SOC benefits from cover crops, as well as which management practices can maximize SOC benefits. To address these questions, we used an advanced process‐based agroecosystem model, ecosys , to assess the impacts of winter cover cropping on SOC accumulation under different environmental and management conditions. We aimed to answer the following questions: (1) To what extent do cover crops benefit SOC accumulation, and how do SOC benefits from cover crops vary with different factors (i.e., initial soil properties, cover crop types, climate during the cover crop growth period, and cover crop planting and terminating time)? (2) How can we enhance SOC benefits from cover crops under different cover crop management options? Specifically, we first calibrated and validated the ecosys model at two long‐term field experiment sites with SOC measurements in Illinois. We then applied the ecosys model to six cover crop field experiment sites spanning across Illinois to assess the impacts of different factors on SOC accumulation. Our modeling results revealed the following findings: (1) Growing cover crops can bring SOC benefits by 0.33 ± 0.06 MgC ha −1 year −1 in six cover crop field experiment sites across Illinois, and the SOC benefits are species specific to legume and non‐legume cover crops. (2) Initial SOC stocks and clay contents had overall small influences on SOC benefits from cover crops. During the cover crop growth period (i.e., winter and spring in the US Midwest), high temperature increased SOC benefits from cover crops, while the impacts from larger precipitation on SOC benefits varied field by field. (3) The SOC benefits from cover crops can be maximized by optimizing cover crop management practices (e.g., selecting cover crop types and controlling cover crop growth period) for the US Midwestern maize–soybean rotation system. Finally, we discussed the economic and policy implications of adopting cover crops in the US Midwest, including that current economic incentives to grow cover crops may not be sufficient to cover costs. This study systematically assessed cover crop impacts for SOC change in the US Midwest context, while also demonstrating that the ecosys model, with rigorous validation using field experiment data, can be an effective tool to guide the adaptive management of cover crops and quantify SOC benefits from cover crops. The study thus provides practical tools and insights for practitioners and policy‐makers to design cover crop related government agricultural policies and incentive programs for farmers and agri‐food related industries.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

The relationship between niche breadth and range size of beech ( Fagus ) species worldwide - Qiong Cai; Erik Welk; Chengjun Ji; Wenjing Fang; Francesco M. Sabatini; Jianxiao Zhu; Jiangling Zhu; Zhiyao Tang; Fabio Attorre; Juan A. Campos; Andraž Čarni; Milan Chytrý; et al. (Journal of Biogeography, 2021)
Aim This work explores whether the commonly observed positive range size–niche breadth relationship exists for Fagus , one of the most dominant and widespread broad‐leaved deciduous tree genera in temperate forests of the Northern Hemisphere. Additionally, we ask whether the 10 extant Fagus species’ niche breadths and climatic tolerances are under phylogenetic control. Location Northern Hemisphere temperate forests. Taxon Fagus L. Methods Combining the global vegetation database sPlot with Chinese vegetation data, we extracted 107,758 relevés containing Fagus species. We estimated biotic and climatic niche breadths per species using plot‐based co‐occurrence data and a resource‐based approach, respectively. We examined the relationships of these estimates with range size and tested for their phylogenetic signal, prior to which a Random Forest (RF) analysis was applied to test which climatic properties are most conserved across the Fagus species. Results Neither biotic niche breadth nor climatic niche breadth was correlated with range size, and the two niche breadths were incongruent as well. Notably, the widespread North American F. grandifolia had a distinctly smaller biotic niche breadth than the Chinese Fagus species ( F. engleriana , F. hayatae , F. longipetiolata and F. lucida ) with restricted distributions in isolated mountains. The RF analysis revealed that cold tolerance did not differ among the 10 species, and thus may represent an ancestral, fixed trait. In addition, neither biotic nor climatic niche breadths are under phylogenetic control. Main Conclusions We interpret the lack of a general positive range size–niche breadth relationship within the genus Fagus as a result of the widespread distribution, high among‐region variation in available niche space, landscape heterogeneity and Quaternary history. The results hold when estimating niche sizes either by fine‐scale co‐occurrence data or coarse‐scale climate data, suggesting a mechanistic link between factors operating across spatial scales. Besides, there was no evidence for diverging ecological specialization within the genus Fagus .

Development and spatial application of a submerged aquatic vegetation model for Cootes Paradise Marsh, Ontario, Canada - Rex W. K. Tang; Susan E. Doka; Jonathan D. Midwood; Jesse M. Gardner Costa (Aquatic Sciences, 2021)

Identification of pleiotropic genes between risk factors of stroke by multivariate metaCCA analysis - Zun Wang; Jonathan Greenbaum; Chuan Qiu; Kelvin Li; Qian Wang; Si-Yuan Tang; Hong-Wen Deng (Molecular Genetics and Genomics, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Straw biochar strengthens the life strategies and network of rhizosphere fungi in manure fertilized soils - Dandan Wang; Na Zhang; Haoqi Tang; Jonathan M. Adams; Bo Sun; Yuting Liang (Soil Ecology Letters, 2019)

Global patterns of Rhododendron diversity: The role of evolutionary time and diversification rates - Nawal Shrestha; Zhiheng Wang; Xiangyan Su; Xiaoting Xu; Lisha Lyu; Yunpeng Liu; Dimitar Dimitrov; Jonathan D. Kennedy; Qinggang Wang; Zhiyao Tang; Xiaojuan Feng (Global Ecology and Biogeography, 2018)
Aim Understanding the evolution of the latitudinal diversity gradient (i.e. increase in species diversity towards the tropics) is a prominent issue in ecology and biogeography. Disentangling the relative contributions of environment and evolutionary history in shaping this gradient remains a major challenge because their relative importance has been found to vary across regions and taxa. Here, using the global distributions and a molecular phylogeny of Rhododendron , one of the largest genera of flowering plants, we aim to compare the relative contributions of contemporary environment, evolutionary time and diversification rates in generating extant species diversity patterns. Location Global. Time period Undefined. Major taxa studied Rhododendron . Methods We compiled the global distributions of all Rhododendron species, and constructed a dated molecular phylogeny using nine chloroplast genes and seven nuclear regions. By integrating these two datasets, we estimated the temporal trends of Rhododendron diversification, and explored the global patterns of its species diversity, net diversification rates, and species ages. Next, we reconstructed the geographical ancestral area of the clade. Finally, we compared the relative contribution of contemporary environment, time‐for‐speciation, and diversification rates on the species diversity pattern of Rhododendron . Results In contrast to the predictions of the time‐for‐speciation hypothesis, we found that although Rhododendron originated at a temperate latitude, its contemporary species diversity is highest in the tropics/subtropics, suggesting an into‐the‐tropics colonization for this genus. We found that the elevated diversification induced by heterogeneous environmental conditions in the tropics/subtropics shapes the global pattern of Rhododendron diversity. Main conclusions Our findings support tropical and subtropical mountains as not only biodiversity and endemism hotspots, but also as cradles for the diversification of Rhododendron . Our study emphasizes the need of unifying ecological and evolutionary approaches in order to gain comprehensive understanding of the mechanisms underlying the global patterns of plant diversity.

Front Cover - Nawal Shrestha; Zhiheng Wang; Xiangyan Su; Xiaoting Xu; Lisha Lyu; Yunpeng Liu; Dimitar Dimitrov; Jonathan D. Kennedy; Qinggang Wang; Zhiyao Tang; Xiaojuan Feng (Global Ecology and Biogeography, 2018)

Longitudinal evaluation of aflatoxin exposure in two cohorts in south-western Uganda - Min-Su Kang; Peter Nkurunziza; Richard Muwanika; Guoqing Qian; Lili Tang; Xiao Song; Kathy Xue; Allan Nkwata; John Ssempebwa; Tom Lutalo; Gershim Asiki; David Serwadda; et al. (Food Additives & Contaminants: Part A, 2015)

Nitrous oxide (N2O) emissions in response to increasing fertilizer addition in maize (Zea mays L.) agriculture in western Kenya - Jonathan E. Hickman; Cheryl A. Palm; Patrick Mutuo; Jerry M. Melillo; Jianwu Tang (Nutrient Cycling in Agroecosystems, 2014)

Vitamin D supplementation does not improve human skeletal muscle contractile properties in insufficient young males - Daniel J. Owens; Daniel Webber; Samuel G. Impey; Jonathan Tang; Timothy F. Donovan; William D. Fraser; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2014)

Differential methylation of the arsenic (III) methyltransferase promoter according to arsenic exposure - Matthew O. Gribble; Wan-yee Tang; Yan Shang; Jonathan Pollak; Jason G. Umans; Kevin A. Francesconi; Walter Goessler; Ellen K. Silbergeld; Eliseo Guallar; Shelley A. Cole; M. Daniele Fallin; Ana Navas-Acien (Archives of Toxicology, 2014)

Ecological Environment Protection in Chinese Rural Hydropower Development Practices: A Review - Xianqiang Tang; Qingyun Li; Min Wu; Wenjian Tang; Feng Jin; Jonathan Haynes; Miklas Scholz (Water, Air, & Soil Pollution, 2012)

At the Biological Modeling and Simulation Frontier - C. Anthony Hunt; Glen E. P. Ropella; Tai Ning Lam; Jonathan Tang; Sean H. J. Kim; Jesse A. Engelberg; Shahab Sheikh-Bahaei (Pharmaceutical Research, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Soil carbon fluxes and stocks in a Great Lakes forest chronosequence - JIANWU TANG; PAUL V. BOLSTAD; JONATHAN G. MARTIN (Global Change Biology, 2009)
We measured soil respiration and soil carbon stocks, as well as micrometeorological variables in a chronosequence of deciduous forests in Wisconsin and Michigan. The chronosequence consisted of (1) four recently disturbed stands, including a clearcut and repeatedly burned stand (burn), a blowdown and partial salvage stand (blowdown), a clearcut with sparse residual overstory (residual), and a regenerated stand from a complete clearcut (regenerated); (2) four young aspen ( Populus tremuloides ) stands in average age of 10 years; (3) four intermediate aspen stands in average age of 26 years; (4) four mature northern hardwood stands in average age of 73 years; and (5) an old‐growth stand approximately 350‐years old. We fitted site‐based models and used continuous measurements of soil temperature to estimate cumulative soil respiration for the growing season of 2005 (days 133–295). Cumulative soil respiration in the growing season was estimated to be 513, 680, 747, 747, 794, 802, 690, and 571 g C m −2 in the burn, blowdown, residual, regenerated, young, intermediate, mature, and old‐growth stands, respectively. The measured apparent temperature sensitivity of soil respiration was the highest in the regenerated stand, and declined from the young stands to the old‐growth. Both, cumulative soil respiration and basal soil respiration at 10 °C, increased during stand establishment, peaked at intermediate age, and then decreased with age. Total soil carbon at 0–60 cm initially decreased after harvest, and increased after stands established. The old‐growth stand accumulated carbon in deep layers of soils, but not in the surface soils. Our study suggests a complexity of long‐term soil carbon dynamics, both in vertical depth and temporal scale.

Shallow Water '06: A Joint Acoustic Propagation/Nonlinear Internal Wave Physics Experiment - Dajun Tang; James Moum; James Lynch; Phil Abbot; Ross Chapman; Peter Dahl; Timothy Duda; Glen Gawarkiewicz; Scott Glenn; John Goff; Hans Graber; John Kemp; et al. (Oceanography, 2007)

Firing rates of pallidal neurons are similar in Huntington’s and Parkinson’s disease patients - Joyce K. H. Tang; Elena Moro; Andres M. Lozano; Anthony E. Lang; William D. Hutchison; Neil Mahant; Jonathan O. Dostrovsky (Experimental Brain Research, 2005)

Evolution of DNA Polymerase Families: Evidences for Multiple Gene Exchange Between Cellular and Viral Proteins - Jonathan Filée; Patrick Forterre; Tang Sen-Lin; Jacqueline Laurent (Journal of Molecular Evolution, 2002)